Finite element dynamic analysis of non-uniform beams on variable one-parameter foundation subjected to uniformly distributed moving loads - Abiala, I.O.; Gbadeyan, J.A. (Zielona Góra: Uniwersytet Zielonogórski)
A general numerical analysis theory capable of describing the behaviour of a non-uniform beam resting on variable one parameter (Winkler) foundation under a uniform partially distributed moving load is developed. The versatile numerical solution technique employed is based on the finite element and Newmark integration methods.
Keywords: finite element; dynamic analysis; non-uniform beams; one-parameter foundation